Physical accessibility to health facilities in Costa Rica - Rosero Bixby, Luis (1993)
This paper estimates physical accessibility to health services in Costa Rican communities and identifies target geographic areas for opening new health facilities. The analyses use geographic information system (GIS) methods and relies on the concept of population potential. The paper aims at illustrating the use of simple GIS techniques for solving an important problem with demographic connotations. Measuring physical access of individuals and populations to health or other public services is crucial in planning the opening of new facilities, evaluating program's impact, and understanding changes in fertility and mortality. Besides, displaying accessibility information on maps is essential to describe a situation, to have a feeling of topological relationships, and to facilitate the use of information by decision makers. Research and evaluation of health and family planning programs have approached the issue of measuring accessibility in a casual way, coming out with common-sense solutions that are far from satisfactory. Some of these common-sense measures of accessibility is the distance to the nearest outlet, the presence of outlets in a community or area, density of services in an area, and the services available in a determined radius. All of these measures have drawbacks that have hampered the inquiries about the relationship between physical access and health and contraceptive behaviour. This paper addresses the following research issues involved in measuring access (National Research Council, 1991): * Contamination across communities: Often people use services located in communities or administrative divisions other than those in which they live.. The lack of services in their communities, or convenience considerations, are causes for this behaviour. Access measures of the type "density of services in an area" do not reflect this contamination effect and can be seriously biased. * Overlapping services: Different organizations may offer similar or related services in a community (e.g., ministry of health, social security, ONGs). This situation -- which is frequent in health services in Latin America -- presents aggregation problems and it is not properly handled by "the nearest outlet" approach. * Competition for services: Access to a clinic will be substantially different if this is the only facility in a big dty than it is in a small town. Competition for services in heavily populated areas reduces the access to them. This circumstance is not considered by only-distance measures of accessibility.